DESCRIPTION OF THE RESPONSE OF ADOLESCENTS WHO HAVE UNWANTED PREGNANCY : LITERATURE REVIEW - Ermiati Ermiati; Ayu Siti Munigar; Erika Enurhasanah; Falaq Aliman; Putri Restu; Dini Aulya S (Journal of Maternity Care and Reproductive Health, 2021)
The high number of unwanted pregnancies in adolescents gives the most significant number of deaths caused by several factors. In facing this case, the adolescents are meeting with two choices; continuing or aborting the pregnancy. This literature review aimed to see the responses of adolescents who experience unwanted pregnancies. The method used is the scoping review approach by following the guidelines for Preferred Reporting items for Systematic Reviews and Meta - Analyzes (PRISMA). The database used by researchers consisted of PubMed, Google Scholar, and ProQuest. The population elements used are adolescents who experience unwanted pregnancy. The researchers obtained 1,410 articles which meet the inclusion criterias are, open access, full text, publication year 2010-2020 and were filtered back into 10 articles for further analysis. Results: From the 10 articles which were analyzed, the responses from adolescents who experienced unwanted pregnancy are; experiencing pressure, sadness, confusion, discomfort, regret, confessing their actions, shame, avoiding the environment, covering up pregnancy, not telling their pregnancy, fear, stress, depression, having an abortion, and it can also lead to a suicide attempt. Conclusion: The unwanted pregnancy responses that appears in adolescents can be concluded into negative responses which cause harm to their pregnancy. Suggestion: Family support is needed so that teenagers who experience the unwanted pregnancy can have a healthy pregnancy.